PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE TPS TERHADAP AKTIVITAS DAN HASIL BELAJAR SISWA - Fina Citha Kasih; Tri Jalmo; Afif Bintoro (Universitas Lampung, 2014)
The objective of this research was to know the use of applicating cooperative learning model think pair share (TPS) toword students activity and students learning result. The research designs were non equivalent pretest – posttest. The research sample were students in X1 and X2 class that was selected by purposive sampling technique. Data of the research were qualitative and quantitative. The qualitative data was gotten by students learning activity and questionnaire that was analyzed descriptively. The quantitative data were the average score of test, that was analyzed by t-test and U-test. The result showed that the students learning activity improve with an average of 79.33 which is in good criteria. The students learning outcomes also develop, with N-gain average score was 40.17. Thus, it can be concluded that the used of TPS model increase with of students learning activity and students learning result in contamination and preservation of environment material.Penelitian ini bertujuan untuk mengetahui penggunaan model pembelajaran TPS terhadap aktivitas dan hasil belajar siswa. Desain penelitian adalah pretes postes tak ekuivalen. Sampel penelitian adalah siswa kelas X1 dan X2 yang dipilih secara purposive sampling. Data penelitian berupa data kualitatif dan kuantitatif. Data kualitatif berupa aktivitas belajar siswa dan angket tanggapan siswa yang dianalisis secara deskriptif. Data kuantitatif diperoleh dari rata-rata nilai tes yang dianalisis menggunakan uji-t dan uji-U. Hasil penelitian menunjukkan aktivitas belajar siswa mengalami peningkatan dengan rata-rata berkriteria baik 79,33. Hasil belajar siswa juga mengalami peningkatan, dengan rata-rata nilai N-gain 40,17. Dengan demikian, pembelajaran menggunakan model TPS berpengaruh terhadap peningkatan aktivitas dan hasil belajar siswa pada materi pencemaran dan pelestarian lingkungan.Kata kunci : aktivitas belajar siswa, hasil belajar siswa, think pair share